Latar Belakang Remaja Melakukan Bullying di Sekolah Menengah Kejuruan (SMK) - Dedeh Juwita Sari; Stefanus Adang Ides; Lina Dewi Anggraeini (Alma Ata University Press, 2017)
The number of casses of violance that occur in school age children today is very worrying for education and parents.This study aimed to determine teenager's background do bullying in vocational school (SMK).The school should be a place to gain knowledge and form a positive personality but currently used as place to do bullying.This study aimed to determine teenager's background do bullying in vocational school (SMK). This research uses qualitative method with phenomenology design which is implemented from July 2016 to May 2017. Informants in this study are vocational students who are still active in school and never do bullying with purposive sampling techniques. Data collection was done by interview and using instrument including interview guidelines, tape recorder handphone. Data analysis used is Colaizzi. The number of respondens in this study was 8 people. From the results of the analysis, there are 10 themes of bullying, democratic parenting, authoritarian parenting, permissive parenting, peer influence, wish to power, fanaticism of differences, facilities and infrastructure, teacher response, and mass media influence. The results of this study concluded that the background of teens bullying can be influenced by family parenting, mass media, peers, and school climate. The suggestion is the instituition educational that can explain about the rules at school and student can receive and understand why the rules should be made.